221k views
3 votes
HELP PLEASE !!! Place each expression under the equivalent expression in the table.

HELP PLEASE !!! Place each expression under the equivalent expression in the table-example-1

2 Answers

5 votes
See the attached figure.
Note: the remaining items can not be put in the table

The detailed solution is as shown in the figures.

HELP PLEASE !!! Place each expression under the equivalent expression in the table-example-1
HELP PLEASE !!! Place each expression under the equivalent expression in the table-example-2
HELP PLEASE !!! Place each expression under the equivalent expression in the table-example-3
User Henningsson
by
5.0k points
3 votes

Answer:

Option 3,5 are under first expression and Option 1,2 are under second expression.

Explanation:

1).
((x-4)(x+2))/(x^(2)+5x+6)+(-3x^(2)+24x-20)/((x+3)(4x-5))


=((x-4)(x+2))/((x+3)(x+2))+(-3x^(2)+24x-20)/((x+3)(4x-5))
=((x-4))/((x+3))+(-3x^(2)+24x-20)/((x+3)(4x-5))


=((x-4)(4x-5)-3x^(2)+24x-20)/((x+3)(4x-5))


=(4x^(2)-5x-16x+20-3x^(2)+24x-20)/((x+3)(4x-5))
=(x^(2)+3x)/((x+3)(4x-5))


=(x(x+3))/((x+3)(4x-5))=(x)/(4x-5)

2).
(3x)/(4x-5)-(4x^(2))/(8x^(2)-10x)=(3x)/(4x-5)-(4x)/(8x-10)
=(3x(8x-10)-4x(4x-5))/((4x-5)(8x-10))


=(24x^(2)-30x-16x^(2)+20x)/((4x-5)(8x-10))


=(8x^(2)-10x)/((4x-5)(8x-10))
=(x(8x-10))/((4x-5)(8x-10))=(x)/(4x-5)

3).
(6x^(2))/(x^(2)-7x+10)/ (2x)/(x-5)


=(6x^(2))/(x^(2)-7x+10)* (x-5)/(2x)


=(3x(x-5))/(x^(2)-7x+10)


=(3x(x-5))/((x-5)(x-2))=(3x)/(x-2)

4).
(-x)/(4x-5)-(4x^(2))/(16x^(2)-22x)


=(-x)/(4x-5)-(2x)/(8x-11)


=(-x(8x-11)-2x(4x-5))/((4x-5)(8x-11))


=(-8x^(2)+11x-8x^(2)+10x)/((4x-5)(8x-11))


=(-16x^(2)+21x)/((4x-5)(8x-11))=(-x(16x-21))/((4x-5)(8x-11))

5).
(3x^(2))/(x+3)* (2(x+3))/(2x^(2)-4x)


=(6x^(2)(x+3))/(2x(x+3)(x-2))=(3x)/(x-2)

6).
(5x^(2))/(x-2)* (2x+6)/(8x^(2)-4x)


=(10x^(2)(x+3))/(4x(x-2)(2x-1))

User Gilberto Alexandre
by
4.9k points